Menelaah Kurikulum Pendidikan Islam dalam Perspektif Sistem Negara Khilafah (Telaah Atas Kitab Al Syakhsiyah Al Islamiyah Karya Taqiyyuddin An Nabhani) - Ahmad Shofiyuddin Ichsan; Fitria Fathurrahman (AL-FURQAN, 2019)
This study aims to elaborate on the Islamic education curriculum according to Taqiyyuddin An Nabhani in the book Al Syakhsiyah Al Islamiyah and the construction of relations in applying the curriculum in the education context in Indonesia. This type of research is qualitative research with library research. The results obtained that the upholding of religion and the application of syar'i laws (including in education) in every affair of life in the khilafah system are mandatory for Muslims with the arguments that are qaṭ'iyyuṡ ṡubūt (exact sources) and qaṭ'iyyud dalālah (clear meanings). It is not possible to do it except with the possession of power. So that in the context of education, the curriculum must include several components, namely goals, content, methods of learning, and evaluation. Whereas in the implementation of the educational curriculum by Taqiyyuddin in Indonesia as a whole it is an impossible thing to happen. However, the existence of various distinctive and different curriculum models provides an opportunity for a country to make comparisons so that it can improve several components in terms of the curriculum itself